Diseño de Estrategias para Optimizar Procesos Logísticos para la Empresa Industrias Metálicas La Roca Ltda., ubicada en la ciudad de Bogotá D.C (2022)
Industrias Metálicas La Roca Ltda was founded in 2009 in the city of Bogotá, is a company dedicated to the marketing of fire equipment and industrial safety. In the work carried out, it was decided tostudy the logistics area of the organization, with the objective of improving the logistics and inventory process, through the implementation of different strategies to achieve the proposed objectives, in the inventory process a relevant improvement was found because the company does not have an updated inventory system and according to its nature since its management is purely manual.